Analysis of a gap-coupled microstrip array antenna - Meshram M.K.; Vishvakarma B.R. (My University, 2025)
In the present paper both theoretical and experimental investigation on gap-coupled microstrip array antenna are presented. Consequently the input impedance, VSWR, bandwidth, etc are evaluated. It is found that gap-coupled array antenna shows marked improvement in VSWR, and bandwidth as compared to conventional microstrip array antenna. Impedance as well as resonant frequency of the gap coupled patch depends heavily on the gap length as well as dielectric constant of the substrate material. © 2001 Taylor & Francis Group, LLC.